Advice-giving roles and strategies in selected faculty member-graduate student advising - Mohd Muzhafar Idrus,; Nor Fariza Mohd Nor,; Ruzy Suliza Hashim,; Raihanah Mohd Mydin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In mentoring graduate students, it is hard to deny the ubiquity of graduate student advising. Faculty members, who are usually engaged in advising to tease out problems and suggest solutions, could often times be faced with negative attributions concerning faculty members’ competence, as well as receive unaligned responses rather than collaborative understanding of issues or recommendations. While previous studies on advising may have focused on specific, intricate, discourse particles and microscopic perspectives on advising, studies on advice giving exchanges that depart from these dimensions are insufficient. To fill in this lacuna, this paper proposes to explore strategies and participation roles in which faculty members assume in selected doctoral dissertation advising. Through discourse analysis, specifically focusing on discourse and situational identities grounded in identities-ininteraction (Zimmerman, 1998), the study illuminates some of the many advising roles and advising strategies that are revealed as legitimate, aligning doctoral student learning experience. In particular, advising roles and advising strategies, as illustrated in this study, link social and institutional context by proposing some of the many trajectories of how both faculty members and graduate students understand the relevance of advising exchanges. By focusing on these exchanges, the paper will also contribute to the growing body of literature on a range of different factors that may constitute advising in terms of content and manner in which advising takes place.